2012
DOI: 10.1097/meg.0b013e3283583c6f
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of endoscopic retrograde cholangiopancreatography

Abstract: The aim of the running benchmarking project in ERCP is to improve patient care in Austria. The survey reflects the general effectiveness and safety of ERCP. The overall complication and success rates are consistent with the available literature data. It sets an example as a benchmarking program that might result in international or even pan-European projects in high-risk endoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 28 publications
3
19
1
1
Order By: Relevance
“…8 9 In this study, where 79.4% of patients were Afro-Caribbean and African Americans of low socioeconomic status, the prevalence of overall complications was 9.8%, which falls within the range of previously reported rates between 4% and 12% in the overall population. [5][6][7][8] However, our reported rate may be lower than the actual number of delayed complications. Though we were able to capture 99.1% of our procedures, we did not have a standard method for collecting data on delayed complications that occurred in patients who presented to other medical institutions or outside providers.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…8 9 In this study, where 79.4% of patients were Afro-Caribbean and African Americans of low socioeconomic status, the prevalence of overall complications was 9.8%, which falls within the range of previously reported rates between 4% and 12% in the overall population. [5][6][7][8] However, our reported rate may be lower than the actual number of delayed complications. Though we were able to capture 99.1% of our procedures, we did not have a standard method for collecting data on delayed complications that occurred in patients who presented to other medical institutions or outside providers.…”
Section: Discussioncontrasting
confidence: 53%
“…4 Other large studies reported complication rates between 4% and 12%. [5][6][7][8] The most common complication is post-ERCP pancreatitis (PEP). Other complications include post-ERCP bleeding, infection, perforation and cardiopulmonary events.…”
Section: Endoscopicmentioning
confidence: 99%
“…The most common complication is post-ERCP pancreatitis (PEP). Among unselected ERCP patients, the PEP rate was 1.8-4.2% [8][9][10]. In a native papilla cannulation, the PEP rate was 5.3% [2] and is rather high 10.8-14.9% in difficult cannulation [1][2][3]11].…”
Section: Ercp (Endoscopic Retrograde Cholangiopancreatography)mentioning
confidence: 95%
“…ERCP is an invasive procedure with an overall complication rate of approximately 4-11% [8][9][10][11]. The most common complication is post-ERCP pancreatitis (PEP).…”
Section: Ercp (Endoscopic Retrograde Cholangiopancreatography)mentioning
confidence: 99%
“…Previous surveys conducted elsewhere [16, 17] have shown that despite robust clinical evidence and published guidelines, most ERCP practitioners do not follow the proposed guidelines. Little is known about the situation in Portugal.…”
Section: Introductionmentioning
confidence: 99%